Investigation on EMF during solubilisation of griseofulvin / Siti Rohaiza Md Saad - Md Saad, Siti Rohaiza (2008)
Solubility is an essential physicochemical property that has to be evaluated during the drug discovery and development process. Our study of interest is to investigate the pattern of electromotive force changes during solubilisation of aqueous insoluble drug, Griseofulvin in the presence of solubility enhancer. The solubility measurements were done by using UV-visible spectroscopy, whereas the emf and pH was analysed by using Automatic Potentiometric Titrator. The experimental data of the solubility study of Griseofulvin in presence of the three different agents (PEG 1500, PEG 4000, PEG 6000) showed varied response in regard to solubility enhancements. It was observed that higher solubility enhancement will correspond to lower value of emf.